Guided bone regeneration with polyethylene membrane, zoledronic acid and hydroxiapatide bone graft in peri-implant bone defect: An experimental study - Yaman, Ferhan; Dundar, Serkan; Cakmak, Omer; Saybak, Arif; Kirtay, Mustafa; Kaya, Beyza; Ozercan, Ibrahim Hanifi (Allied Acad, 2017)
This study aimed to determine the guided bone regeneration (GBR) capacity of peri-implant bone defect treatment, either with only a hydroxyapatite bone graft or with a hydroxyapatite bone graft mixed with zoledronic acid (ZA) and employing polyethylene glycol (PEG) barrier membranes. In this study, four male New Zealand rabbits were used. First, the rabbits were randomly divided into two groups, the hydroxyapatite graft group (HA) (n=2) and the HA graft + zoledronic acid group (HA+ZA) (n=2). For the HA group, peri-implant GBR was performed with only an HA bone graft, and a resorbable PEG barrier membrane was placed over each surgical defect to cover the peri-implant bone defects. For the HA+ZA group, peri-implant GBR was performed with an HA bone graft that had previously been mixed with ZA. A resorbable PEG barrier membrane was placed over each surgical defect to cover the peri-implant bone defects. Experiments were performed using a standardised peri-implant bone tissue defect model in rabbit tibia for 60 days. Circumferential defects were surgically induced around the dental implants on the tibias of four rabbits. Sixty days after the surgical procedures, the rabbits were sacrificed, and their tibias with the graft sites were harvested for histologic evaluation. In the HA+ZA group, significantly more new bone formation was detected as compared with the HA group (P<0.05). Within the limitations of this study, locally administered ZA with an HA synthetic graft and PEG membrane was a more effective method as compared to using only a graft in a peri-implant GBR procedure. Additionally, a PEG membrane should be useful in GBR as a barrier membrane. Further studies are needed to confirm these results.
Keywords: Periimplant bone defect; Guided bone regeneration; Synthetic bone graft; hydroxiapatide; Zoledronic acid